Relationship Between Paraphrasing Ability and Grammar Mastery of English Education Students at Universitas Negeri Padang - Saputri, Elika Oktavia; Ovilia, Ririn (Universitas Negeri Padang, 2024)
In order to fulfil the requirements of academic papers, students are intended to compose their works by drawing upon concepts acquired from a range of sources that they have studied. Paraphrasing is one of the advanced academic skills which it can be employed during academic writing. Nevertheless, in reality, the majority of students continue to struggle with paraphrasing and their proficiency in this skill remains limited. Multiple studies have examined the difficulties encountered by students in the process of paraphrasing, revealing that grammar mastery is one of the predominant challenges in this context. This correlational study seeks to ascertain the correlation and quantify the impact of students' grammar mastery toward their ability to paraphrase. The study population consists of eight classes of second-year students in the English Education study-program at Universitas Negeri Padang who are enrolled in the Academic Writing course. The sample for this study was selected using cluster random selection, with two classes being chosen. Grammar test (TOEFL) and paraphrasing test (articles from reputable journal) are the instrument for this study. This study employed quantitative research methodology, utilizing bivariate correlation analysis technique. The results indicate a positive correlation between students’ paraphrasing ability and their grammar mastery. The findings also demonstrate that grammatical mastery accounted for 29.2% of the variation in paraphrase ability.